In silico screening of natural compounds to inhibit interaction of human ACE2 receptor and spike protein of SARS-CoV-2 for the prevention of COVID-19. Issue 2 (22nd January 2023) - Sharma, Priyanka; Joshi, Tanuja; Joshi, Tushar; Mathpal, Shalini; Maiti, Priyanka; Nand, Mahesh; Chandra, Subhash; Tamta, Sushma
Abstract: A computational investigation was carried out to find out potential phytochemicals that could inhibit the binding of human angiotensin-converting enzyme-2 (ACE2) receptors to spike protein of SARS-CoV-2 which is an essential step to gain entry inside human cells and onset of viral infection known as Coronavirus disease (COVID-19). A library of phytochemicals was screened by virtual screening against ACE2 receptors resulting in twenty phytochemicals out of 686 which had binding energy (−11.8 to −6.9 kcal/mol). Drug-likeness gave five hits, but ADMET analysis yielded 4 nontoxic hit phytochemicals. Molecular dynamics simulation of four-hit compounds resulted in acceptable stability and good dynamics behavior. These phytochemicals are Hinokinin, Gmelanone, Isocolumbin, and Tinocordioside, from Vitis vinifera, Gmelina arborea, and Tinospora cordifolia . The above-mentioned phytochemicals may be promising ACE2 inhibitors and can prevent infection of SARS-CoV-2 by inhibiting the entry of the virus into host cells. Communicated by Ramaswamy H. Sarma